Isolation, characterization, and identification of cellulolytic bacteria from household compost for cellulase production - T. Q. Truong; K. D. Nguyen (The Ukrainian Biochemical Journal)
Using microorganisms for waste treatment is a growing trend that offers numerous economic and environmental benefits. This study aimed to evaluate the characteristics of cellulolytic bacterial strains isolated from compost samples from household waste. Biochemical and molecular tests were conducted to identify highly cellulolytic bacteria. Thirty aerobic strains were isolated, of these three isolates (WS1.7, WS3.1, and WS3.29) demonstrated high extracellular cellulase activity and decomposed 51.34–63.43% of the filter paper mass after 7 days of incubation in a liquid medium. Based on their colony morphology and biochemical properties, these three isolates were predicted to belong to the genus Bacillus. The maximum endoglucanase activity of the crude enzyme produced by Bacillus velezensis WS1.7 was demonstrated. These findings indicate the potential of the B. velezensis WS1.7 isolate for further research and cellulase production.